Water demand and need of irrigation for the grapevine in Urussanga, SC - Back, Alvaro José (2021)
The article aimed to evaluate the irrigation requirements for grapevine crops under the climaticconditions of the southern coast of the State of Santa Catarina, Brazil, through the serial water balance. Data from the meteorological station of Urussanga (latitude 28o31' S, longitude 49o19' W, altitude 49m) for the 1981- 2004 period were used. Crop evapotranspiration reference was determined by Penman-Monteith's method. Simulations of water balance identified water demands and irrigation needs in 10-day periods. Water balancewithout irrigation was simulated to determine the relative grapevine crop production. The results showed that water consumption for grapevine crop was 335mm and, even without irrigation, the average grapevine crop production was above 90% of the potential production.